Suggestions for a National Exhibition of Scottish Portraits in Edinburgh, in the year 1855; including a communication on the subject from Thomas Carlyle (Proceedings of the Society of Antiquaries of Scotland, 1855)
Secretary David Laing returned to the proposal for a National Portrait Gallery of Scotland. He presented a letter from historian and essayist Thomas Carlyle on the subject. Carlyle highlights the importance of portraiture for encouraging an interest in history, as well as the artistic value of displaying portraits. He makes the point that the selection of whose portraits to include will be key to the success of the gallery. He ends his letter with some recommendations on how the gallery should be created and run. David Laing then requests that this idea be put before the Board of Trustees again and suggests that a committee should be formed to make enquiries about portraits that might be included. His proposals were approved by the members. Meeting notes for 10 July, 1854 are appended.